Training Exercises on Modern Ukrainian Literary Language in Future Philologist’s Professional Preparation (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article a role of training exercises on modern Ukrainian literary language in future philologist’s professional preparation has been determined, an expediency of their introduction in the practice of higher school has been proved.
Keywords: exercises; training exercises; lexicology; phraseology